2014
DOI: 10.1111/1750-3841.12582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intramuscular Fat, Breed, and Age at Slaughter on Fatty Acid Composition in Green Hams

Abstract: Knowledge of age-related changes and breed differences in fat content and composition would be helpful in determining the optimal breed and slaughter time in terms of raw ham quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For instance, the compositional distribution of lipids in pig muscle correlates with intramuscular fat content (IMF, also referred to as marbling). Specifically, the deposition of FA classes when neutral lipid content is adjusted for IMF fractionation as a covariate suggests that deposition of SFA and MUFA increases significantly with age from 6 to 9 months, whereas that of PUFA decreases significantly [ 3 ]. For complex phenotypes such as porcine IMF content and its FA composition, in a previous study based on a hierarchical clustering analysis [ 4 ], we have shown that lipogenic-related genes are in general positively correlated with MUFA, while the lipolytic-related genes are specifically positively correlated with PUFA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the compositional distribution of lipids in pig muscle correlates with intramuscular fat content (IMF, also referred to as marbling). Specifically, the deposition of FA classes when neutral lipid content is adjusted for IMF fractionation as a covariate suggests that deposition of SFA and MUFA increases significantly with age from 6 to 9 months, whereas that of PUFA decreases significantly [ 3 ]. For complex phenotypes such as porcine IMF content and its FA composition, in a previous study based on a hierarchical clustering analysis [ 4 ], we have shown that lipogenic-related genes are in general positively correlated with MUFA, while the lipolytic-related genes are specifically positively correlated with PUFA.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough description of the animals, rearing and feeding conditions, preslaughter handling and slaughter is given by Storrustløkken et al . (). In brief, a 3 × 3 matrix was designed with the Norwegian pig breeds Landrace (LR), Duroc (DU) and Hampshire (HS), and the slaughter ages 6, 7.5 and 9 months.…”
Section: Methodsmentioning
confidence: 97%
“…The lipids were fractionated into neutral lipids (NL), phospholipids (PL) and free fatty acids (FFA) as described by Storrustløkken et al . (). After fractionation, the lipids were evaporated to dryness under a jet of nitrogen at 37 °C prior to derivatization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation